Penerapan Metode Permainan "Polisi Numpang Tanya" Dalam Pembelajaran IPS Siswa Usia 9-10 Tahun di Desa Gombang - Kartika Diyana; Umi Sholihah; Jajang Susatya (WIDYA DIDAKTIKA - Jurnal Ilmiah Kependidikan, 2023)
In learning, a media is needed to support teaching and learning activities so that it is easier and more effective in delivering material by educators and receiving material by students. This research is to find out the application of the game method "Police Numpang Tanya" in social studies learning for students aged 9-10 years in Gombang village. This study uses a qualitative approach. A qualitative approach is used as information relating to the improvement or enhancement of the learning process. The research design used is descriptive. This method is carried out by describing a symptom, event, incident that is happening at the present time. The results of the study showed that the learning process using the Police Numpang Tanya Game Method in Social Studies Learning for Students Age 9-10 in Gombang Village experienced an increase in the average score from 51.5 to 62.